1I/'Oumuamua as an N2 Ice Fragment of an exo‐Pluto Surface: I. Size and Compositional Constraints. Issue 5 (13th May 2021) - Jackson, Alan P.; Desch, Steven J.
Abstract: The origin of the interstellar object 1I/'Oumuamua has defied explanation. We perform calculations of the non‐gravitational acceleration that would be experienced by bodies composed of a range of different ices and demonstrate that a body composed of N2 ice would satisfy the available constraints on the non‐gravitational acceleration, size, and albedo, and lack of detectable emission of CO or CO2 or dust. We find that 'Oumuamua was small, with dimensions 45 m × 44 m × 7.5 m at the time of observation at 1.42 au from the Sun, with a high albedo of 0.64. This albedo is consistent with the N2 surfaces of bodies like Pluto and Triton. We estimate 'Oumuamua was ejected about 0.4–0.5 Gyr ago from a young stellar system, possibly in the Perseus arm. Objects like 'Oumuamua may directly probe the surface compositions of a hitherto‐unobserved type of exoplanet: "exo‐plutos". In a companion paper (Desch & Jackson, 2021) we demonstrate that dynamical instabilities like the one experienced by the Kuiper belt, in other stellar systems, plausibly could generate and eject large numbers of N2 ice fragments. 'Oumuamua may be the first sample of an exoplanet brought to us. Plain Language Summary: 1I/'Oumuamua is very strange and it is hard to explain where it came from. We looked at several different ices and the push they would give 'Oumuamua as they evaporated. We found that the best ice is nitrogen (N2 ), which would explain many of the things we know about it. 'Oumuamua was small, about half as long as a city block and only as thick as a three story building, but it was very shiny. The shininess is about the same as the surfaces of Pluto and Triton, which are also covered in nitrogen ice. We suggest 'Oumuamua was probably thrown out of a young star system about half a billion years ago. Bodies like 'Oumuamua may allow us to see what the surfaces of a so far unknown type of exoplanet, "exo‐Plutos, " are made of. In a following paper (Desch & Jackson, 2021) we show that orbital instabilities in which giant planets move around, as happened in our own outer solar system 4 billion years ago, could make and throw out large numbers of small pieces of nitrogen ice like 'Oumuamua. 'Oumuamua may be the first piece of an exoplanet brought to us. Key Points: A fragment of N2 ice would satisfy all known constraints on 'Oumuamua's size, composition, and acceleration The presence of N2 ice in the solar system on Pluto makes it likely 'Oumuamua is such a fragment The existence of "exo‐Plutos" in other stellar systems must be common